2021
DOI: 10.48550/arxiv.2111.00807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superfluidity and Quantum Geometry in Twisted Multilayer Systems

Abstract: Designer 2D materials where the constituent layers are not aligned may result in band structures with dispersionless, "flat" bands. Twisted bilayer graphene has been found to show correlated phases as well as superconductivity related to such flat bands. In parallel, theory work has discovered that superconductivity and superfluidity is determined by the quantum geometry and topology of the band structure. These recent key developments are merging to a flourishing research topic: understanding the possible con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 149 publications
1
15
0
Order By: Relevance
“…A very intriguing experimental platform to test our results is twisted bilayer graphene [26][27][28][29][30][31][32][33].…”
Section: B Outlookmentioning
confidence: 90%
See 1 more Smart Citation
“…A very intriguing experimental platform to test our results is twisted bilayer graphene [26][27][28][29][30][31][32][33].…”
Section: B Outlookmentioning
confidence: 90%
“…Its imaginary part is the well established Berry curvature characterizing the topological phase of the band, while its real part is the quantum metric. The study of the quantum metric, and thus also the quantum geometric tensor, has attracted attention on many fronts in the recent past including superconducting systems [6][7][8][9], quantum phase transitions [10,11], magnetic signatures [12][13][14][15], quantum topology and geometry [16][17][18][19][20], flat band systems [21], in nonadiabatic evolution [22], as marker distinguishing insulators from metals [23], non-hermitian systems [24,25], in twisted bilayer graphene [26][27][28][29][30][31][32][33] and in dimensions higher than two [34][35][36][37][38][39][40][41]. Theoretical measurements have been proposed and measurements of the quantum geometric tensor have been performed in [42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…We now discuss lower bound of superfluid weight within the mean-field approximation. We adopt the exact-flat-band approximation [49,[60][61][62][63], where we choose the normal-state flat bands to be exactly-flat. By using the formalism of Euler obstructed Cooper pairing, we obtain a lower bound for the trace of the zerotemperature superfluid weight for the C 2z T -invariant pairing in Eq.…”
Section: Bounded Superfluid Weightmentioning
confidence: 99%
“…In a flat band the effective mass m * diverges and one would expect the superfluid weight to vanish. On the contrary, it has been found that, besides the band dispersion, also the quantum geometry of the Bloch wave functions contributes to the superfluid weight [24][25][26][27][28][29][30][31][32][33]. In particular, in the case of a well isolated flat band the superfluid weight originates purely from the quantum geometry and can be written as…”
mentioning
confidence: 99%